Does expression choice affect the analysis of light spectrum and facial emotion recognition?. (April 2018) - Fotios, S; Castleton, H; Yang, B
Facial emotion recognition has been used as a representative pedestrian activity in studies examining the effect of changes in road lighting. Past studies have drawn conclusions using results averaged across performance with the six universally recognised expressions. This paper asks whether expression choice matters. A reanalysis of past data for each unique expression does not suggest a change in the conclusion that facial emotion recognition is not significantly affected by the spectral power distribution of the lighting.